2021
DOI: 10.3390/cells10082029
|View full text |Cite
|
Sign up to set email alerts
|

Physcion Induces Potential Anticancer Effects in Cervical Cancer Cells

Abstract: Background: The extent of morphological and ultrastructural changes in HeLa cells was assessed by optical, fluorescence and electron microscopy after exposure to various concentrations of physcion, taking into account the biological properties of the test compound. Methods: Cell viability was assessed by MTT assay, while the cell cycle, LC3 expression, apoptosis, change of mitochondrial potential, Bcl-2 protein expression level and the level of reactive oxygen species were analyzed by flow cytometry. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Such properties are also demonstrated by other anticancer drugs with a different mechanism of action, such as cisplatin, 47 imatinib, 48 sorafenib, 49 obatoclax, 50 etoposit, or camptothecin‐DNA damaging drugs 44 . Cytotoxic effects against tumor cell lysosomes and the property of inducing autophagy have also been shown by anthraquinones that have been the subject of our previous studies, that is, aloe‐emodin, 51 emodin, 52 chrysophanol, 53 physcion, 54 including also the rhein presented in this paper.…”
Section: Discussionmentioning
confidence: 75%
“…Such properties are also demonstrated by other anticancer drugs with a different mechanism of action, such as cisplatin, 47 imatinib, 48 sorafenib, 49 obatoclax, 50 etoposit, or camptothecin‐DNA damaging drugs 44 . Cytotoxic effects against tumor cell lysosomes and the property of inducing autophagy have also been shown by anthraquinones that have been the subject of our previous studies, that is, aloe‐emodin, 51 emodin, 52 chrysophanol, 53 physcion, 54 including also the rhein presented in this paper.…”
Section: Discussionmentioning
confidence: 75%
“…Additionally, Geriyol et al [ 58 ] and Mhaidat et al [ 59 ] demonstrated the genotoxic effect of Vinca alkaloids without double-stranded DNA breaks. The literature shows that other anthraquinones also exhibit genotoxicity, e.g., chrysophanol [ 60 ], physcion [ 61 ], aloe-emodin [ 62 , 63 ], danthron [ 64 ], and emodin, which is the subject of our research, and which, thanks to its structure, can easily penetrate between the adenine and thymine of the DNA double helix [ 65 ]. ATM kinase plays a key role in the response to DNA damage; however, attention is currently being paid to its important role as a modulator of oxidation (in response to stress), and as a modulator of mitochondrial homeostasis and apoptosis [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study also showed that topical administration of red ginseng rhizomes (2 mg/mouse) and ginsenoside Ro (0.2 mg/mouse) induced hair regrowth in testosterone-treated mice [50]. Physcion, a component of Polygonum multiforum (PM), has anti-inflammatory, antioxidant, and anticancer effects [192,193]. Treatment with physcion exhibited hair growth-promoting activity in testosterone-treated C57BL/6 mice [51].…”
Section: α-Reductase Inhibitory Effectmentioning
confidence: 96%